Pengaruh Pemberian Ekstrak Buah Pohon Andalas (Morus Macroura Miq.) terhadap Gambaran Histopatologi Miokardium pada Tikus Model Aterosklerosis - Intan Putri Syamtoni; Henny Mulyani; Rita Hamdani; Noza Hilbertina; Miftah Irramah; Endrinaldi Endrinaldi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Atherosclerosis is an inflammation that occurs in blood vessels, especially arteries, it could be developed by an accumulation of lipids in the body, which is atherosclerosis causes this to become a major factor of cardiovascular disease. The fruit of the andalas contains flavonoid, morasin C and M for anti-inflammatory. The purpose of this experimental is to see the effect of extract andalas fruits to histologial changes in myocardium of rats with aterosclerosis model. This research was an experimental study with a randomized post test only control group design with using 29 mice which have been divided into 5 groups, there is negative control group (K-), positive control group (K+), treatment group 1 (P1), treatment group 2 ( P2), and treatment group 3 (P3). The results measurement of the weight rat's heart after analysis used the One Way ANOVA test were p = 0.000, that’s mean there was a significant difference of weight rat's heart in each other groups. Measuring the thickness of myocardial cell size used the One Way Anova test, the resulted is p = 0.632, that’s mean there was no relationship between the groups. Measuring the blood vessel thickness were used by One Way ANOVA analysis, the resulted is p = 0.301, that’s mean there was no significant difference in arterial blood vessel thickness in all groups. The conclusion of this study is there was changes in rat heart weight in all groups, there was no significant change in the histopathological size of the myocardium in all groups, lipofuscin was found in 1 sample, necrosis wasn’t found, sicatric tissue wasn’t found, and there was no significant change in the histopathological picture of arterial thickness in this experience.